IMPLEMENTASI AKAD ISTISHNA’ PADA TRANSAKSI JUAL BELI FURNITURE DITINJAU DARI PERSFEKTIF EKONOMI ISLAM (Studi Kasus Usaha Furniture Kec. Kolaka) - Nur Intan; Muhammad Asra; Ibrahim Tawile (IAI Al-Mawaddah Warrahmah Kolaka, 2020)
Implementation of the istishna contract in furniture buying and selling transactions. In the furniture business in Kolaka District, purchases are made by ordering goods with a price agreement between producers and consumers. With a payment system that is made partly at the beginning as a down payment, in the middle when the goods are being produced, and when the goods are one hundred percent finished or when the goods are delivered to the house. The system for ordering goods carried out by the Kolaka District furniture business uses the purchase method with the istishna contract. The practice of ordering goods transactions in two ways. First, go to the store directly to make a purchase by ordering goods. Second, ordering can be made by telephone, via WA (Whats App) by sending the desired image or explaining the specifications of the item you want to order, be it size, color, material to be used, and others. Payment can be made on the spot or transfer via bank account.